The Use of Purple Eggplant as a Wheat Flour Substitution Ingredient in Making Cookies - Zana Zuflia; Vany Octaviany (Jurnal Indonesia Sosial Teknologi, 2024)
The background of this study is based on the high nutritional content of purple eggplant, such as fiber, vitamins, and antioxidant compounds, which have the potential to increase the nutritional value of cookies while reducing the use of wheat flour. The purpose of this study is to develop a healthier cookie formulation by utilizing purple eggplant as a partial substitution ingredient for wheat flour, as well as to evaluate its organoleptic quality and nutritional content. The method used is an experimental method with a complete random design (RAL). The manufacturing process includes processing purple eggplant into flour, formulation of ingredient mixtures, and organoleptic testing with trained panelists. Organoleptic testing involves assessing the taste, aroma, texture, and color of cookies. The results showed that the substitution of wheat flour with purple eggplant flour of up to 30% produced cookies with a crispy texture, sweet-medium taste, and a distinctive aroma that was liked by the panelists. The fiber and protein content of cookies is also significantly increased compared to cookies without substitution. In conclusion, the use of purple eggplant as a substitute for wheat flour in making cookies provides better nutritional benefits without reducing product acceptability. This innovation offers a potential healthy food alternative to be further developed in the snack food industry.